2002
DOI: 10.5488/cmp.5.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Star Polymer/Water Solutions: New Experimental Findings

Abstract: The purpose of the present work is to highlight a number of recent experimental results that have contributed significantly to the research area of star polymer. Firstly we will refer to a very impressive SANS work by J.Peyrelasse, C.Perreur, J.-P.Habas and J.François which is focused on the study of the structural properties of aqueous solutions of a star copolymer of PEO and PPO by Small Angle Neutron Scattering. Next, we will refer to some experimental advances reported in the work by R.Triolo, V.Arrighi, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Our data also demonstrated that nature of the polymer backbone is sufficiently amphiphilic for self‐assembly, and that there is an equilibrium between molecular unimers and aggregates in solution. Our results are consistent with earlier studies showing that there is an equilibrium between unimers and aggregates in a solution containing 4‐arm star block copolymer, sP(EO‐block‐PO) . In addition, our results are supported by studies showing that both linear block copolymers and linear gradient copolymers of EO and PO undergo self‐assembly …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our data also demonstrated that nature of the polymer backbone is sufficiently amphiphilic for self‐assembly, and that there is an equilibrium between molecular unimers and aggregates in solution. Our results are consistent with earlier studies showing that there is an equilibrium between unimers and aggregates in a solution containing 4‐arm star block copolymer, sP(EO‐block‐PO) . In addition, our results are supported by studies showing that both linear block copolymers and linear gradient copolymers of EO and PO undergo self‐assembly …”
Section: Resultssupporting
confidence: 92%
“…Our results are consistent with earlier studies showing that there is an equilibrium between unimers and aggregates in a solution containing 4-arm star block copolymer, sP(EO-block-PO). [38] In addition, our results are supported by Reactive polymers are then prepared by endcapping the hydroxy terminated polymer HO-sP(EO-stat-PO) with IPDI. Hydrolysis of the isocyanate groups first leads to the formation of carbamic acid and amino groups.…”
Section: Self-assembly Of Nanogelssupporting
confidence: 58%
“…Strongly temperature dependent micellization and gelation of these amphiphilic copolymers have been thoroughly examined in the last few decades though mostly on linear PEO–PPO–PEO triblock copolymers and there exist several reviews [ 1 , 15 , 16 ]. However, only a few authors have reported on the aqueous solution behavior of their star shaped counterparts [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…While previous SANS studies on this Tetronic have been reported in the literature, they were specifically focused on the structure of the gel phase under flow. [29][30][31][32] This is the first structural study covering the micelles from the dilute to the concentrated regime including the gel phase, through the combined use dynamic light scattering (DLS), small-angle neutron scattering (SANS), steady-state and time-resolved fluorescence,…”
mentioning
confidence: 99%